A smooth startup strategy for hybrid MMC based HVDC systems. (December 2021) - Xu, Luona; Luo, Yongjie; Song, Yonghui; Blaabjerg, Frede
Highlights: A semi-controlled charging method is presented for firing IGBTs. A group modulation method for HMMC with unbalanced voltages is proposed. An improved AC-side startup method is proposed to suppress the inrush current. Abstract: Hybrid modular multilevel converter (HMMC) topology consisting of full-bridge submodules (FBSMs) and half-bridge submodules (HBSMs) is one of the promising technical solutions for long-distance high voltage direct current (HVDC) power transmission systems. However, the HMMC has very different charging circuit characteristics from the conventional half-bridge MMC (HB-MMC) topology and suffers from low and unbalanced precharge capacitor voltages and surge current when starting from the AC-side, due to its hybrid submodule configuration. In this paper, an AC-side startup scheme for the HMMC is proposed, including an additional semi-controlled charging process and an improved controlled charging method, which allows the HMMC to smoothly charge its submodule capacitors and establish the DC-link voltage without requirements of auxiliary sources. The improved controlled charging method is composed of a group modulation and a group voltage balancing control strategies, which enables the HMMC to operate stably with enhanced AC voltage output capability under the condition of low and unbalanced capacitor voltage in the HBSM group and FBSM group, thereby eliminating converter overmodulation and surge current during the startup procedures. In addition, DC-side startup strategy is also discussed in this paper. PSCAD/EMTDC simulation results based on a practical ±200 kV/750 MW HMMC-HVDC system demonstrate the effectiveness of the proposed method.